2021
DOI: 10.1016/j.jhepr.2021.100351
|View full text |Cite
|
Sign up to set email alerts
|

Excellent outcomes with liver transplantation in hepatopulmonary syndrome across pre-transplant PaO2 spectrum

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
(34 reference statements)
0
7
0
3
Order By: Relevance
“… 63 Although post-LT survival was lower in patients with PaO 2 <45 mmHg, the outcomes were still good, given the median survival of 11.5 years, compared to 14.1 years in patients with PaO 2 ≥45 to <50 mmHg. 63 In any case, patients with severe HPS should be referred to specialised high-volume LT centres, with experience of treating severe post-LT hypoxemia.…”
Section: Management and Treatment Optionsmentioning
confidence: 97%
See 4 more Smart Citations
“… 63 Although post-LT survival was lower in patients with PaO 2 <45 mmHg, the outcomes were still good, given the median survival of 11.5 years, compared to 14.1 years in patients with PaO 2 ≥45 to <50 mmHg. 63 In any case, patients with severe HPS should be referred to specialised high-volume LT centres, with experience of treating severe post-LT hypoxemia.…”
Section: Management and Treatment Optionsmentioning
confidence: 97%
“…A recent study, extending the UNOS database study through 2019, found that overall survival was not different between patients with PaO2 <45 mmHg, 45 to <60 mmHg and ≥60 mmHg [63]. Although post-LT survival was lower in patients with PaO2 <45 mmHg, the outcomes were still good, given the median survival of 11.5 years, compared to 14.1 years in patients with PaO2 ≥45 to <50 mmHg [63]. In any case, patients with severe HPS should be referred to specialized highvolume LT centers, experienced with post-LT interventions to treat severe post-LT hypoxemia.…”
Section: Liver Transplantationmentioning
confidence: 97%
See 3 more Smart Citations